Free‐of‐charge dispensing of antipsychotics for schizophrenia in Denmark: Impact on the nationwide prescription registry and redemption of somatic medications. Issue 4 (5th August 2022) - Rohde, Christopher; Højlund, Mikkel; Gasse, Christiane; Hallas, Jesper; Köhler‐Forsberg, Ole
Abstract: Objective: Free‐of‐charge dispensing of antipsychotics for schizophrenia was introduced in Denmark around 2008. However, free‐of‐charge dispensing is not recorded in the Danish National Prescription Register (DNPR), potentially introducing bias and misclassification. Methods: We identified all 30 275 individuals with a first‐episode schizophrenia diagnosis in Denmark between 1 January 1999 and 1 March 2017 including all redeemed prescriptions registered in the DNPR during the 2 years after the schizophrenia diagnosis. For each calendar year, we calculated the proportion of individuals who had filled ≥1 prescription for psychotropic and/or somatic medications within the first 2 years after the schizophrenia diagnosis. Results: From 2007 to 2017, the proportion of individuals with prescription‐records for any psychotropic medication during the 2 years after the schizophrenia diagnosis decreased from 88% to 74%, particularly antipsychotics (from 83% to 61%) and antidepressants (from 49% to 35%). This was particularly observed among those aged 18–30 years at the schizophrenia diagnosis. A similar decrease was not observed for prescription‐records of somatic medications. Conclusion: The introduction of free‐of‐charge antipsychotics has affected the redemption of specific psychotropic drugs in the DNPR in first‐episode schizophrenia. This limitation needs to be considered in register‐based studies and emphasizes the need to identify solutions.